Metabolic liver inflammation in obesity does not robustly decrease hepatic and circulating CETP. (August 2018) - Blauw, Lisanne L.; Li, Zhuang; Rensen, Sander S.; Greve, Jan Willem M.; Verhoeven, Aswin; Derks, Rico J.; Giera, Martin; Wang, Yanan; Rensen, Patrick C.N.
Abstract: Background and aims: We recently showed that plasma cholesteryl ester transfer protein (CETP) is mainly derived from VSIG4-positive Kupffer cells. Activation of these cells by the bacterial endotoxin lipopolysaccharide (LPS) strongly decreases CETP expression. As Kupffer cell activation plays a detrimental role in the progression of non-alcoholic fatty liver disease (NAFLD), we aimed to study if metabolic liver inflammation is also associated with a decrease in hepatic and circulating CETP. Methods: We collected plasma and liver biopsy samples at various stages of NAFLD from 93 obese individuals who underwent bariatric surgery. Liver lobular inflammation was histologically determined, and liver CETP expression, CETP positive cells, circulating CETP concentrations, and liver VSIG4 expression were quantified. Results: Mean (SD) plasma CETP concentration was 2.68 (0.89) μg/mL. In the presence of liver inflammation, compared to the absence of pathology, the difference in hepatic CETP expression was −0.03 arbitrary units (95% CI -0.26, 0.20), the difference in number of hepatic CETP positive cells (range 11–140 per mm 2 ) was −20.0 per mm 2 (95% CI -41.6, 1.9), and the difference in plasma CETP was −0.35 μg/mL (95% CI -0.80, 0.10). Hepatic VSIG4 expression was not associated with liver inflammation (0.00; 95% CI -0.15, 0.15). Conclusions: We found no strong evidence for a strong negative association between metabolic liver inflammation and CETP-related outcomes in obese individuals, although we observed consistent trends. These data indicate that metabolic liver inflammation does not mimic the strong effects of LPS on the hepatic expression and production of CETP by Kupffer cells. Highlights: It has been shown that cholesteryl ester transfer protein (CETP) is mainly derived from a specific subset of Kupffer cells in the liver. Activation of these cells by the bacterial endotoxin lipopolysaccharide (LPS) strongly decreases CETP expression. Kupffer cell activation plays a detrimental role in the progression of non-alcoholic fatty liver disease (NAFLD). We determined if metabolic liver inflammation, as a component of NAFLD, is also associated with less hepatic CETP expression in humans. We found no strong evidence for a negative association between metabolic liver inflammation and CETP. Our results indicate that metabolic liver inflammation does not mimic the strong effects of LPS on the hepatic expression and production of CETP by Kupffer cells.